Effects of Slingshot with Relative Intensity on Repetitions to Failure, Myoelectric Activity, and Perception of Effort During the Bench Press Exercise in Recreationally Trained Men - Paulo H. Marchetti; Roberto A. Magalhaes; Willy A. Gomes; Luis F.M. Teixeira; Gustavo H. dos Santos; Rafael C. Paulino; Josinaldo J. da Silva (International Universities Strength and Conditioning Association, 2024)
The purpose of this study was to evaluate the effects of the slingshot (SS) with relative similar intensity on repetitions to failure at 70%1RM (RF70%1RM), myoelectric activity (sEMG), and perception of effort (sRPE) during the bench press exercise in recreationally-trained men. Sixteen recreationally-trained men (31.7±7.1years, 173.2±6.0cm, 85.4±15.9kg) performed the 1RM test with SS and without SS. Then, all subjects performed RF70%1RM in two experimental conditions: with (WSS) and without (WTSS) the slingshot device. sEMG of the pectoralis major (PM), anterior deltoid (AD), lateral head of triceps brachii (TL), and long head of triceps brachii (TLO) was measured during both experimental conditions. sRPE was measured after both experimental conditions. Two-way ANOVAs (2x3) were used to test differences between conditions (WSS and WTSS) and muscle groups (PM, AD, TL, TLO) for iEMG and peak RMS. A paired t-test was used to measure differences between RF70%1RM (WSS and WTSS) and sRPE. Statistical difference was observed between RF70%1RM (WSS > WTSS, p=0.015). Statistical difference was observed between conditions for PM (peak RMS: WTSS > WSS, p=0.05). Statistical differences were observed for PM (iEMG: WTSS > WSS, p=0.05) and TLO activation (iEMG: WTSS > WSS, p=0.044). In conclusion, the use of the SS device induced a greater number of repetitions to failure and less myoelectric activation for the pectoralis major and long head of the triceps brachii. The perception of effort was similar between experimental conditions.